Longitudinal predictors of change in self-reported personal wellbeing in a cohort of Australian people who inject drugs - Carrotte, E.; Scott, N.; Higgs, Peter; Cogger, S.; Stoove, M.; Aitken, C.; Dietze, P. (Wiley-Blackwell Publishing Ltd., 2015)
Introduction and Aims: Cross-sectional research has identified correlates of personal wellbeing scores in people who inject drugs (PWID). This study aims to identify longitudinal predictors of change in the personal wellbeing of a cohort of P WID. Design and Methods: Participants were 757 PWID enrolled in the Melbourne Injecting Drug User Cohort Study. We used gender-stratified linear models with fixed effects for each participant to examine correlates of change in individual score s on the Personal Wellbeing Index (PWI) over time. Further linear regression of adjusted PW I scores was used to measure correlations bet ween demographic variables. Results: The cohort’s mean PWI score was consistent across the first four interview waves, between 54.8/100 and 56.0/100 – 26-28% lower than general Australian population scores (76.0/100). However, individual PWI scores varied significantly. A key predictor of a decline in PWI score was being assaulted in the past six months. Among women, intentionally overdosing in the previous 12 months and increased blood-borne virus transmission risk behaviour were associated with declines in PWI scores, while enrolling in OST was associated with an increase in PWI score. Among men, moving into unstable housing, injecting more frequently and recently overdosing on heroin were associated with declines in PWI scores, while becoming employed between interview waves was associated with an increase in PWI score. Discussion and Conclusions: Our participants experience significantly lower levels of personal wellbeing than the general Australian population, influenced by assault, overdose and other harms. We must continue targeted efforts to improve wellbeing among PWID.